2019
DOI: 10.1016/j.ajo.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Macula Vessel Density and Thickness in Early Primary Open-Angle Glaucoma

Abstract: Purpose: To characterize and compare the ganglion cell complex (GCC) thickness and macula vessel density in pre-perimetric and early primary open angle glaucoma (POAG) eyes. Design: Cross-sectional study. Methods: 57 healthy eyes, 68 pre-perimetric and 162 early POAG eyes enrolled in the Diagnostic Innovations in Glaucoma Study. Optical coherence tomography angiography (OCT-A) based superficial macula vessel density and OCT based GCC thickness were evaluated simultaneously. Percent loss from normal of GCC thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 45 publications
10
78
4
1
Order By: Relevance
“…Evaluations of the macular VD parameters in PPG eyes were not extensive [8,26,29,30]. Our study showed significant macular microvasculature dropout in PPG and early PG eyes, which was supported by Hou et al [30] and Poli et al [29].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Evaluations of the macular VD parameters in PPG eyes were not extensive [8,26,29,30]. Our study showed significant macular microvasculature dropout in PPG and early PG eyes, which was supported by Hou et al [30] and Poli et al [29].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported that the AUROC values for macular VD that ranged from 0.562 to 0.800 for distinguishing between early glaucoma and normal eyes [26,27,30,34]. However, little is known about the diagnostic ability of macular VD in detecting PPG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations